Fault Trace Corrugation and Segmentation as a Measure of Fault Structural Maturity - I. Manighetti; A. Mercier; L. De Barros (Geophysical Research Letters)
Abstract As faults grow over time and become more “mature,” some of their geometrical and mechanical properties evolve, and these changes modify earthquake behavior. It is thus of prime importance to know the degree of structural maturity of a fault that is likely to produce large earthquakes. Although this concept is extensively used, there is no common definition or metric to measure the structural maturity of a fault. We analyzed the heterogeneity of the surface traces of 13 large seismogenic faults whose maturity is known qualitatively. We measured the corrugations and step‐over segmentation of the traces from ∼100 m to the fault length scale. Corrugations and some properties of the segmentation are found to vary with fault structural maturity. We provide scaling relationships that quantify the structural maturity of a fault based on its surface trace. These results should help in parameterizing source faults in earthquake models.